The Impact of Social Media on Workplace Culture - S.Baqutayan, Dr. Shadiya Mohamed; Al-Hamami, Nasser Mohammed (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Social media has begun long time ago, and recently has immeasurable popularity across the globe. People tended to use this technology in making new friends, keeping up with their own friends, and most significantly sharing experiences and making life easy with the information gain from this new technology. Certainly, the most common reason for using this technology are communication and collaborations, and surrly, the reason is because it is the most easiest way to build relationships in disperses social communities. Sampling of 81-employees and managers assigned from organizations worldwide. Hence, their impact of social media networking technology on workplace culture were measured. The aim of this research was to assess the impact of media networking on employees behaviour, job satisfaction and performance. Eventually, the result indicated that social media networking technology have great impact on employee behavior, performance, and job satisfaction. This outcome will help employee to managed their work, gain competitive advantage for business organizations, and definitely help them establish and maintain their company’s reputation, granting them more confidence, successful, and effectual ways of working.